(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
To analyze the characteristics of clinical manifestations occurring against the background of combined cardiovascular and renal dysfunctions in elderly patients.